Annotated checklist of Georgian oribatid mites - Murvanidze, Maka; Mumladze, Levan (Zootaxa, 2016)
A new updated checklist of Georgian oribatid mites is based on the critical review of existing literature data and new findings. The list includes 534 oribatid species of which 21 species are new for the country recorded from more than 390 locations. For each species information of the global and regional distribution is presented with notes on ecological characteristics. As far as necessary we provide remarks on taxonomic issues to overcome the ambiguities and inconsistencies existing in literature.